Providing services for acute low-back pain: A survey of Australian physiotherapists. (April 2016) - Keating, Jennifer L.; McKenzie, Joanne E.; O'Connor, Denise A.; French, Simon; Walker, Bruce F.; Charity, Melanie; Page, Matthew J.; Green, Sally E.
Abstract: Objective: To determine whether physiotherapists avoid lumbar X-rays for acute non-specific low back pain and advise people to stay active. Methods: We conducted a cross sectional survey of Australian physiotherapists. 880 physiotherapists were randomly sampled from Victoria (495), South Australia (158), and Western Australia (227). Physiotherapists were asked which investigations they would order and interventions they would provide for five acute low back pain (LBP) presentations described in vignettes. Four of the five vignettes represented people who would not require a plain lumbar X-ray and would benefit from advice to stay active; one described a patient with a suspected vertebral fracture and would require a plain X-ray. Participants selected from a list of response options or provided free text responses. Results: Questionnaires were completed by 203 of 567 potentially eligible physiotherapists (response rate 36%). Across the four vignettes where an X-ray was not indicated, 75% (95%CI 71–78%) of physiotherapists reported they would practice concordant with the guidelines and not order an X-ray, and 62% (95%CI 57–66%) provided advice to stay active. Conclusions: Most physiotherapists report intended compliance with recommendations in Australian clinical practice guidelines (CPGs) regarding avoiding the use of X-rays and providing advice to stay active for people with simple acute low back pain, given a vignette based scenario. The majority of respondents reported that they would not advise bed rest. Possible opportunities to further enhance compliance need to be developed and tested to reinforce the role of CPGs in informing physiotherapy practice. Highlights: Vignettes provided a strategy for estimating likely compliance with clinical practice guidelines (CPGs). We examined compliance with Australian CPGs for simple acute low back pain. Most physiotherapists would not advise bed rest. Most would avoid X-rays and provide advice to stay active. Strategies to further enhance compliance need to be developed and tested.